Evolution of nanomechanical properties and crystallinity of individual titanium dioxide nanotube resonators. (17th January 2018) - Stassi, Stefano; Lamberti, Andrea; Roppolo, Ignazio; Casu, Alberto; Bianco, Stefano; Scaiola, Davide; Falqui, Andrea; Pirri, Candido Fabrizio; Ricciardi, Carlo
Abstract: Herein a complete characterization of single TiO2 nanotube resonator was reported for the first time. The modal vibration response analysis allows a non-invasive indirect evaluation of the mechanical properties of the TiO2 nanotube. The effect of post-grown thermal treatments on nanotube mechanical properties was investigated and carefully correlated to the chemico-physical parameters evolution. The Young's modulus of TiO2 nanotube rises linearly from 57 GPa up to 105 GPa for annealing at 600 °C depending on the compositional and crystallographic evolution of the nanostructure. Considering the growing interest in single nanostructure devices, the reported findings allow a deeper understanding of the properties of individual titanium dioxide nanotubes extrapolated from their standard arrayed architecture.